2018
DOI: 10.1589/jpts.30.1355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orbicularis oris muscle training on muscle strength and lip closure function in patients with stroke and swallowing disorder

Abstract: [Purpose] We aimed to investigate the effect of resistance training of the orbicularis oris muscles on lip muscle strength and closure function in patients with swallowing disorder with facial palsy after stroke. [Participants and Methods] This study recruited 10 patients with swallowing disorder and facial palsy after stroke. All the participants received orbicularis oris muscle training at an intensity of 70% of 1 repetition maximum by using an Iowa oral performance instrument. Muscle strength and lip closur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Seven studies reported interventions aimed at remediation of facial palsy as their primary objective (6, 26-29, 31, 33), and six reported targeting lip function or movement in the context of post-stroke dysphagia therapy (13,16,23,30,32,34). Four studies reported on active intervention methods for remediation of oromotor function or facial palsy (23,(26)(27)(28); two used muscle strengthening exercises alone (26,27) and the other two used biofeedback (via mirror or device) while performing orofacial exercises (23,28). Four studies reported on passive intervention techniques such as massage, stretching or electrical stimulation for the remediation of facial muscle strength or facial palsy (13,16,29,30).…”
Section: Types Of Physical Rehabilitation For Facial Palsymentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies reported interventions aimed at remediation of facial palsy as their primary objective (6, 26-29, 31, 33), and six reported targeting lip function or movement in the context of post-stroke dysphagia therapy (13,16,23,30,32,34). Four studies reported on active intervention methods for remediation of oromotor function or facial palsy (23,(26)(27)(28); two used muscle strengthening exercises alone (26,27) and the other two used biofeedback (via mirror or device) while performing orofacial exercises (23,28). Four studies reported on passive intervention techniques such as massage, stretching or electrical stimulation for the remediation of facial muscle strength or facial palsy (13,16,29,30).…”
Section: Types Of Physical Rehabilitation For Facial Palsymentioning
confidence: 99%
“…Four studies reported on active therapy methods; one RCT (23), one nRCT (28), and two case series' (26,27). All four studies reported improvements in treatment variables measured.…”
Section: Active Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…13 The effectiveness of this muscle in speech, nutrition, and swallowing functions has also been reported in various studies. 14,15 Based on all this information, changes in the musculoskeletal system are inevitable with increasing age. However, studies in the literature on viscoelastic and tone properties of orbiculari oris muscle are rare.…”
mentioning
confidence: 99%